Hydrothermal liquefaction of jatropha curcas (J. curcas) under subcritical water conditions: Water and palm oil mill effluent as solvents - Rohazriny, Rohim; Khairuddin, Md Isa; Umi Fazara, Md Ali; Mohd Aizudin, Abd Aziz; Naimah, Ibrahim; Muhammad Auni, Hairunnaja; Saiful Azhar, Saad; Nur Amira Fatihah, Bashari (John Wiley and Sons Inc, 2025)
In this study, palm oil mill effluent (POME) and water were used as the medium or hydrogen donor solvent in the hydrothermal liquefaction (HTL) of Jatropha curcas. POME, with its high organic compound content, is seen as a promising solvent to be investigated. The POME analysis using GC–MS showed the existence of palmitic and oleic acids. The HTL was performed for both solvents using a batch reactor, and three parameters were varied (biomass-to-solvent ratio, temperature, and reaction time). The results showed that POME could be used as a medium for the HTL of J. curcas. It was found that the HTL of J. curcas with POME produced a higher oil yield (63.4%) than the one using water (43.2%) with a lower biomass-to-solvent ratio (1:2) and lower temperature (300°C) with an optimum reaction time (60 min), and with 30.8% of solid and 5.8% of gas recorded. The results of gas chromatography–mass spectrometry (GC–MS) showed that high ester content and the lowest acid content were obtained at 350°C for both solvents. As for POME, the ester content increased at 350°C while the acid content decreased at the same temperature. High hydrocarbon content was obtained for the experiment at 300°C for both solvents. The highest oil yield under POME conditions recorded a good HHV value of 39.07 MJ/kg with an oxygen content of ~11%, with 81% carbon recovered, indicating high energy recovery. The extra hydrogen generated through the reforming of POME in the liquefaction of J. curcas leads to stabilizing the free radicals and producing high oil yields.